The provision of teaching/learning materials in Swaziland high schools - Magagula, Cisco (University of the Free State, 2005)
This study set out to establish whether there was any government policy regarding the provision of textbooks and stationery to high school learners in Swaziland; to determine whose responsibility it was to provide learners with these materials, and to assess the system used by high schools to give learners access to them. The study found that there was no government policy regulating the provision of textbooks and stationery to learners in high schools; that parents were solely responsible for providing such materials, and that most high schools used the book loan system (which has its advantages and disadvantages, and should be refined) to give learners access to the requisite materials.

Die doel van hierdie studie is om vas te stel of daar enigsins ’n regeringsbeleid bestaan vir die voorsiening van handboeke en skryfbehoeftes aan hoërskoolleerlinge in Swaziland; om te bepaal wie verantwoordelik is vir die voorsiening van handboeke en skryfbehoeftes aan hoërskoolleerlinge in Swaziland en om te bepaal watter stelsel deur hoërskole gebruik word om leerlinge toegang tot handboeke en skryfbehoeftes te gee. Uit die studie is die volgende bevindings gemaak: daar bestaan geen regeringsbeleid ten opsigte van die regulering en voorsiening van handboeke en skryfbehoeftes aan leerlinge in hoërskole nie; ouers is ten volle verantwoordelik vir die voorsiening van handboeke en skryfbehoeftes aan leerlinge en die meeste hoërskole maak gebruik van die boekleenstelsel om leerlinge toegang tot handboeke en skryfbehoeftes te verleen. Die boekleenstelsel het voor- en nadele wat verder ondersoek en verfyn moet word.
Keywords: Government policy, Swaziland; High school learners; Provision of textbooks; Stationery to learners; Academic achievement